Impact of Rheumatic Process in Left and Right Ventricular Function in Patients with Mitral Regurgitation - Estu Rudiktyo; Emir Yonas; Maarten J. Cramer; Bambang B. Siswanto; Pieter A. Doevendans; Amiliana M. Soesanto (Ubiquity Press, 2023)
Background: Mitral regurgitation (MR) burdens the left and right ventricles with a volume or pressure overload that leads to a series of compensatory adaptations that eventually lead to ventricular dysfunction, and it is well known that in rheumatic heart disease (RHD) that the inflammatory process not only occurs in the valve but also involves the myocardial and pericardial layers. However, whether the inflammatory process in rheumatic MR is associated with ventricular function besides hemodynamic changes is not yet established. Purpose: Evaluate whether rheumatic etiology is associated with ventricular dysfunction in patients with chronic MR. Methods: The study population comprised patients aged 18 years or older included in the registry who had echocardiography performed at the National Cardiovascular Center Harapan Kita in Indonesia during the study period with isolated primary MR due to rheumatic etiology and degenerative process with at least moderate regurgitation. Results: The current study included 1,130 patients with significant isolated degenerative MR and 276 patients with rheumatic MR. Patients with rheumatic MR were younger and had a higher prevalence of atrial fibrillation and pulmonary hypertension, worse left ventricle (LV) ejection fraction and tricuspid annular plane systolic excursion (TAPSE) value, and larger left atrium (LA) dimension compared to patients with degenerative mitral regurgitation (MR). Gender, age, LV end-systolic diameter, rheumatic etiology, and TAPSE were independently associated with more impaired LV ejection fraction. Whereas low LV ejection fraction, LV end-systolic diameter, and tricuspid peak velocity (TR) peak velocity >3.4 m/s were independently associated with more reduced right ventricle (RV) systolic function (Table 3). Conclusions: Rheumatic etiology was independently associated with more impaired left ventricular function; however, rheumatic etiology was not associated with reduced right ventricular systolic function in a patient with significant chronic MR.